2022
DOI: 10.1021/acsapm.2c01157
|View full text |Cite
|
Sign up to set email alerts
|

Thiol-Functionalized Hybridized Porous Polymer on Polyurethane Foam for Recyclable Adsorption of Multiple Ions

Abstract: The pollutants in the excessive discharge of industrial and daily wastewater, which contain multiple metal ions and anions, will cause irreversible damage to the environment and human body. However, current adsorbents only possess adsorption ability toward single type of ion, thus greatly limiting the adsorption efficiency. In this work, we prepared thiol functionalized poly(di(4-vinylpyridine)-zinc chloride-co-divinylbenzene) (Poly-(ZnVP 2 -co-DVB)-SH) with a semicoordinated structure, coordinated/covalent hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 72 publications
1
0
0
Order By: Relevance
“…As shown in Figure b,e, the XPS spectrum of N elements of GL-Fe 3 O 4 -TEA shows peaks at 397.44 and 401.35 eV corresponding to Fe–N and C–N from TEA . In comparison, the XPS spectrum of GL-Fe 3 O 4 -NH 3 presents only the peak at 399.45 eV assigned to the C–N bond from the PU sponge . Combining the above results, it is concluded that the coordination of Fe ions and TEA took place.…”
Section: Resultssupporting
confidence: 51%
“…As shown in Figure b,e, the XPS spectrum of N elements of GL-Fe 3 O 4 -TEA shows peaks at 397.44 and 401.35 eV corresponding to Fe–N and C–N from TEA . In comparison, the XPS spectrum of GL-Fe 3 O 4 -NH 3 presents only the peak at 399.45 eV assigned to the C–N bond from the PU sponge . Combining the above results, it is concluded that the coordination of Fe ions and TEA took place.…”
Section: Resultssupporting
confidence: 51%